The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.15244/pjoes/61626
|View full text |Cite
|
Sign up to set email alerts
|

Chromium (VI) Adsorption Characteristics of Bentonite Under Different Modification Patterns

Abstract: We investigated the Cr(VI) adsorption characteristics of bentonite under different modifi cation patterns by using a mixture of BS-12 (dodecyl dimethyl betaine) and DTAB (dodecyl trimethyl ammonium bromide). DTAB was used to compositely modify 25%, 50%, and 100% BS-12-modifi ed bentonite (three modifi ed modes of bentonite with BS-12). In addition to these modifi cation modes, variations as functions of pH value, temperature, and ionic strength were compared. Results showed: 1. Cr(VI) adsorption capacity of be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The result showed that the amount of fluoride adsorbed on fired clay pot was significantly affected when the concentration increases from 0 to 1000 mg/L KNO 3 . The same effect of ionic strength was also observed for the adsorption of Cr(VI) on bentonite [40]. Studying the influence of ionic strength is a simple approach to distinguish between inner sphere and outer sphere surface complexes when direct evidence from microscopic data is absent.…”
Section: Effect Of Ionic Strengthsupporting
confidence: 55%
“…The result showed that the amount of fluoride adsorbed on fired clay pot was significantly affected when the concentration increases from 0 to 1000 mg/L KNO 3 . The same effect of ionic strength was also observed for the adsorption of Cr(VI) on bentonite [40]. Studying the influence of ionic strength is a simple approach to distinguish between inner sphere and outer sphere surface complexes when direct evidence from microscopic data is absent.…”
Section: Effect Of Ionic Strengthsupporting
confidence: 55%
“…Liu [ 41 , 42 ] found that modified bentonite with amphoteric surfactants was effective at adsorbing bisphenol A, Pb 2+ , and Cd 2+ . This was probably due to the carboxyl groups (−COO−) and positively charged groups (−N + ) that were present in the amphoteric surfactants, which make it simpler to adsorb metal ions and organic contaminants [ 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the numerous physical, chemical and biological methods for the removal of Cr(VI) compounds from aqueous solutions, the adsorption method is the applicable method based on its simplicity and costeffectiveness. Various numbers of different materials such as natural clays (Zachara et al, 1988;Ajouyed et al, 2011;Li et al, 2016;Algamal et al, 2018), natural zeolites (Faghihian & Bowman, 2005;Jorfi et al, 2017), agricultural and industrial waste material (Šćiban & Klašnja, 2002), different carbon materials, activated carbon (Mohan & Pittman, 2006) etc. were tested as an adsorbent for Cr(VI) compounds from aqueous medium.…”
Section: Introductionmentioning
confidence: 99%